Insights into the environmental reservoir of pathogenic Vibrio parahaemolyticus using comparative genomics - Hazen, Tracy H.; Lafon, Patricia C.; Garrett, Nancy M.; Lowe, Tiffany M.; Silberger, Daniel J.; Rowe, Lori A.; Frace, Michael; Parsons, Michele B.; Bopp, Cheryl A.; Rasko, David A.; Sobecky, Patricia A. (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus is an aquatic halophilic bacterium that occupies estuarine and coastal marine environments, and is a leading cause of seafood-borne food poisoning cases. To investigate the environmental reservoir and potential gene flow that occurs among V. parahaemolyticus isolates, the virulence-associated gene content and genome diversity of a collection of 133 V. parahaemolyticus isolates were analyzed. Phylogenetic analysis of housekeeping genes, and pulsed-field gel electrophoresis, demonstrated that there is genetic similarity among V. parahaemolyticus clinical and environmental isolates. Whole-genome sequencing and comparative analysis of six representative V. parahaemolyticus isolates was used to identify genes that are unique to the clinical and environmental isolates examined. Comparative genomics demonstrated an O3:K6 environmental isolate, AF91, which was cultured from sediment collected in Florida in 2006, has significant genomic similarity to the post-1995 O3:K6 isolates. However, AF91 lacks the majority of the virulence-associated genes and genomic islands associated with these highly virulent post-1995 O3:K6 genomes. These findings demonstrate that although they do not contain most of the known virulence-associated regions, some V. parahaemolyticus environmental isolates exhibit significant genetic similarity to clinical isolates. This highlights the dynamic nature of the V. parahaemolyticus genome allowing them to transition between aquatic and host-pathogen states.